Finite Element Modelling of Aeolian Vibrations on Stranded High-voltage OHL Conductors - AlAqil, M.A; Kopsidas, K (IET Conference Proceedings, 2018)
The problem of Aeolian vibrations has been studied in indoor test-spans for many years. Its relevant standard experimentations have resulted in introducing the Energy Balance Method (EBM) which is the most commonly implemented method in the industry. Besides conductor properties, aerodynamic forces (Lift and Drag forces) acting on the conductor are the main input data for the EBM. The existing models frequently use experimental data of Lift and Drag forces for a cylinder. To further investigate the capabilities of wind-conductor interaction numerical modelling, it is useful to take advantage of Finite Element Modelling techniques. This paper simulates the wind flow around single OHL conductors with different outer layer stranding shapes and sizes utilizing COMSOL Multiphysics software. The simulations are based on solving the NavierStokes equation to compute the aerodynamic forces by integration of the pressure and shear forces within the boundaries of the conductor geometry. The numerical model computes the aerodynamic forces for three conductor geometries including smooth-surface, round-stranded, and trapezoidal stranding shapes. The numerically obtained solutions show that less aerodynamic forces are experienced by rounds and trapezoids compared to the cylinder geometry. This observation is true for high Reynolds numbers.